Training for volunteers at the University of Granada - Albina Khasanzyanova (Universidad de Granada, 2011)
The present work should be treated as a "progress report" prior to the comparative study that the author has been developing in her master's degree program about the training for university students volunteers in various countries in Europe. The present report describes the case of the University of Granada, including in this overview of the history of Granada institution, foundations and frames that will generate, in the subsequent thesis, the relevant comparative analysis.